The Effect of Work Motivation and Discipline on Employee Performance: Study at a Government Agency in West Java Province - Syarah Maulidina Nurfadllika; Ujang Wawan Sam Adinata (Jurnal Computech & Bisnis (e-Journal), 2023)
The present research examined the influence of work motivation and discipline on employee performance within a governmental organization in the West Java province. The study investigated the predominant factor affecting job performance in the agency above. Specifically, the research examined whether motivation or discipline has a more significant impact on employee performance. The sample size for the study consisted of 58 employees who were surveyed using a questionnaire. The research utilized path analysis to establish the authenticity of motivation and work discipline variables in a government agency in West Java Province. The results highlight the importance of prioritizing work motivation and discipline to improve employee performance. The research findings underscored the substantial impact of motivation (X1) and work discipline (X2) on the performance of employees (Y). The results indicate that motivation contributed more significantly than the other factor. This suggests that the organization could enhance employee performance by promoting motivation and addressing their needs, which would positively impact their performance. Although motivation has a more significant impact than work discipline, the latter still holds significant importance as a fundamental component. The agency can achieve the enhancement of employee performance through the implementation of regulatory compliance, the reevaluation of existing protocols, the imposition of penalties for non-compliance, and the provision of incentives for those who exhibit work discipline. Cultivating a solid work ethic is of utmost importance as it reflects adherence to workplace regulations and individual accountability, thereby directly influencing achieving maximum employee productivity. As a result, a positive correlation exists between high levels of discipline and maximum work productivity.